The Implementation of Social Education Learning Based on Multicultural Education in SMP Negeri 1 Lasem - Asmarani, Kartika; Wasino, Wasino; Subagyo, Subagyo (Universitas Negeri Semarang, 2018)
The diversity of religion, ethnic, and culture that has been owned by the students of SMP Negeri 1 Lasem impacts the social patterns either in school or outside the school. The interest of social education learning is still not enough. One of social education concepts from NCSS is culture. This is really related to multicultural education. The aims of this research are to know the multicultural values in Lasem society, to analyze the implementation of social education based on multicultural education in SMP Negeri 1 Lasem also to know the supporting and obstacle factor in the implementation of social education based on multicultural education in SMP Negeri 1 Lasem. The research method that is applied is qualitative research. The multicultural values in Lasem Society are humanity values, tolerance value, mutual help value, justice value, and mutual cooperation value. Method that is applied in social education learning based of multicultural values in SMP Negeri 1 Lasem is contribution method. The supporting factors are religion factor, ethnic factor, culture factor, the support from local communities, mutual respect and respecting the others. The obstacle factors here are the relationship between students that sometimes get crashed when discussion happened in class, the characteristic of students which are difference to each other, the motivation to study, the understanding of tolerance in religion and the lack of school properties and also the lack of competence of a social education teacher.